Family role in the human development sustained in Perú - Arellano, Martha (2001)
The family main role in Perú and anywhere else is significant because their members are assured satisfy their main needs and promote the adequate conditions towards whole maturity or their abilities and help foster society´s development. This article also analyses woman situation and her roles in global society: in culture, in institutions and as a person, in the sustained human development that allows intergenerational analysis.